Collaborative Online Learning: Plurilingual and Pluricultural Development - O. Polyakova; I. N. Goryacheva; R. Galstyan-Sargsyan (Высшее образование в России)
Background. The growing importance of international cooperation among universities have increased the number of joint training projects. Common Bologna principles followed by Russian and Spanish tertiary institutions helped perform a pilot study focused on telecollaboration and plurilingual and pluricultural competence implementation. The project aimed at forming plurilingual and pluricultural competence and communicative competence among students studying either English or Spanish or both through the integration of digital technologies into the learning process.Methods. This 7-month study took place in Moscow (Russian Federation) and Valencia (Spain) from November 2019 to June 2020. Participants were university students aged 20–23 from Teaching Training Faculties from Lomonosov Moscow State University and CEU Cardenal Herrera University. The undergraduates who volunteered to participate in the focus group took part in five telecollaboration sessions (March-May 2020). The participants were divided into two mixed (50% Russian and 50% Spanish learners) subgroups and discussed suggested topics during online studentled bilingual sessions. After each online interaction, researchers collected their opinions through questionnaires and discussion with a lecturer.Outcomes. All participants announced that the study gave them a chance to improve their language abilities, update their vocabulary and enhance their intercultural experience. None of the partakers reported having experienced any difficulty doing the project and only regretted that interaction time was too short. Additionally, lecturers were able to test new curricula implementation and assessment procedures.Conclusions. The pilot study was feasible to deliver and there was a clear, satisfactory result with the focus groups participants and teaching staff.